Qualitative characterization of nitrogen-containing compounds in jet and diesel fuel extracts by using (+) electrospray ionization coupled to a linear quadrupole ion trap/orbitrap mass spectrometer. (15th July 2023) - Romanczyk, Mark; Loegel, Thomas N.; Myers, Kristina M.
Graphical abstract: Highlights: High resolution mass spectrometry facilitated thorough chemical characterization of nitrogen-containing compounds. At least ten and eleven different chemical classes of nitrogen-containing compounds were present in jet fuels and diesel, respectively. Kendrick mass defect plots enable easy comparison of compositional differences of the jet and diesel samples. Collision-activated dissociation demonstrated efficacy at providing structural information and isomeric differentiation. Abstract: The development of analytical methods for the characterization of nitrogen-containing compounds (NCCs) in liquid transportation fuels are critical, as these compounds adversely affect fuel storage and thermal stability. In this work, (+) electrospray ionization coupled to a linear quadrupole ion trap/orbitrap mass spectrometer provided detailed chemical analysis of the NCCs in jet and diesel fuels. Upon methanol extractions of the individual fuels (three jet fuels and one diesel), the methanol layer was diluted and injected into the ESI source where protonation was the dominant ionization reaction for the NCCs, which exhibited little to no fragmentation. Kendrick mass defect plots were constructed to facilitate chemical characterization. Many chemical classes of NCCs ( i.e., alkylamines, pyridines, indoles, quinolines, carbazoles) were identified in the jet and diesel fuel extracts. Compositional differences were observed when the jet fuel extracts were compared to each other and when compared to the diesel extract. For example, the most abundant NCCs in Jet fuel 1 had empirical formulas of Cn H(2n) N (decahydroquinolines/decahydroisoquinolines) and Cn H(2n-6) N (indolines/tetrahydroquinolines/tetrahydroisoquinolines). Conversely, the most abundant NCCs in Jet fuel 2 had empirical formulas of Cn H(2n-6) N and Cn H(2n-10) N (quinolines/isoquinolines/naphthylamines) while the most abundant NCCs in Jet fuel 3 had empirical formulas of Cn H(2n+4) N (alkylamines). The ionized NCCs derived from the jet fuels had wider carbon number ranges than compared to those reported in previous studies. The average molecular weights, ring and double bond equivalent values and total carbon numbers for the ionized NCCs in the four extracts ranged from 192.8–215.3 Da, 1.7–5.0 and 13.5–14.8, respectively. Further, the average carbon number for each homologue ion series (ions with the same empirical formula but differ by 14 Da) were determined. Collision-activated dissociation was also investigated to evaluate its efficacy at providing structural elucidation and isomeric differentiation for ionized NCCs. Overall, the high-resolution mass spectrometry measurements provided thorough chemical characterization that may aid in linking NCC compositions to storage and thermal stability failures and advance the current understanding of issues concerning fuel incompatibility upon the mixing of different fuels.